The transition of humanity from a predominantly cohesive energy system to one of predominantly negative energy. And then what? - Caravedo, Baltazar (2022)
Abstract: To answer the question, and then what? it is first necessary to ask ourselves how we appeared on Earth and how we got to where we are; then to answer what happens today; and, finally, to try to establish how our disturbed human system might unfold in the future. Development and preparation of this document use a complex systems perspective. The link between human system components is considered as a social energy that can unite or repel. The greater the cohesion energy, the greater the adaptive capacity of the system; its continuity implies transformation. Entropic energy leads to collapse. The human system historical deployment has generated changes in the predominance of cohesion and repulsion energies that have manifested themselves in the pattern of bonds., Entropic energy has been enhanced with the appearance of the COVID-19 pandemic. The same goes for the growth of mental disorders and the use of fossil energy. To mitigate its negative impact, it is necessary to change the components’ role and their behavior logic.